Utilization of Digital Technology in the Learning Process in Elementary Schools: A Literature Review of Challenges and Opportunities for Teachers - Rahmat Purnomo (PT. Anagata Sembagi Education, 2024)
The digital transformation in education has driven significant changes in learning approaches in elementary schools. This study aims to critically examine the use of digital technology in elementary school learning through a literature review of the challenges and opportunities faced by teachers. The method used is a qualitative study with a literature review approach, which collects and analyzes various scientific sources from journals, proceedings, and academic books published in the last five years. The results of the study indicate that digital technology can improve learning effectiveness, facilitate more interactive and contextual learning, and encourage the development of 21st-century competencies in students. However, its implementation still faces significant challenges, particularly in aspects of teacher readiness, infrastructure gaps, and limited professional training. This study also highlights the importance of a TPACK-based pedagogical approach, supportive school leadership, and educational policies that are responsive to technological developments. Thus, the results of this study provide a conceptual contribution to the development of digital learning practices in elementary schools and can serve as a reference in formulating adaptive and sustainable educational strategies in the digital era.